Pengaruh Pemahaman dan Regiulitas Mahasiswa terhadap Minat Berwakaf Uang - Fadila Oktarina; Lisa M.N Puspita (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
According to the Indonesian Waqf Board (BWI), cash waqf in Indonesia is currently still minimal, especially cash waqf, estimated to reach 180 trillion rupiah per year but only realized at 1.4 trillion or 2.52% as of March 2022. The low realization of cash waqf potential also reflects the low interest of the community which is certainly caused by various factors. Therefore, this study aims to further examine the factors that are thought to affect the interest in waqf money. This study aims to analyze and predict the effect of religiosity and understanding on the intention to endow money. This type of research is quantitative research with the objects to be studied, namely understanding, religiosity, and interest in waqf money. The population in this study were students of the Faculty of Economics and Business, Bengkulu University using multiple linear regression analysis methods and using a correlation approach. The results of this study indicate that (1) Religiosity has a positive effect on interest in waqf money, (2) Understanding waqf has a positive effect on interest in waqf money.